Influence of socioeconomic status on in-hospital mortality and morbidity after stroke in India: Retrospective hospital-based cohort study - Ravi Yadav; Kameshwar Prasad; Vasantha M Padma; Achal Kumar Srivastava; Manjari Tripathi; Rohit Bhatia (Wolters Kluwer Medknow Publications, 2013)
Objectives : To determine an association between socioeconomic status and in-hospital outcome in Indian patients with stroke. Materials and Methods : Retrospective hospital-based cohort study. The hospital stroke register was used for this study. The independent variables were demographic job status, education, cardiovascular risk factors, comorbidities and the score on the Glasgow Coma Scale (GCS). The outcome variables were mortality and Barthel's index (BI) score at discharge. Results : Data of 599 consecutive patients comprising 370 men (54.3%) and 229 women (33.6%) was available for analysis. Their mean age was 55.63±15.36 years. Age, diagnosis (ischemic or hemorrhagic), midline shift, smoking and GCS were significantly associated with mortality and BI score (P<0.05). There was a statistically significant association between employment status and BI at discharge (P=0.03) in univariate analysis. In multivariate analysis, joblessness was associated with lower BI at discharge (P=0.02) after adjustment for GCS motor score and stroke subtype. Conclusion : Our study shows that in patients with stroke, lower employment status is associated with poor outcome at discharge from the hospital. The association is independent of other prognostic factors.